Efforts to Improve Mathematical Communication Skills With The Application of the TTW Learning Strategy - Panjaitan, Hendrik; Sihaloho, Binner (Yana Research, 2023)
This study aims to improve students' mathematical communication abilities and find out what efforts can be made to overcome the mathematical communication difficulties experienced by students in prisms and pyramids teaching materials in class VIII-B of SMP Negeri 23 Medan, 2022/2023 Academic Year. This type of research is Classroom Action Research (CAR). The subjects in this study were 27 class VIII-B students of SMP Negeri 23 Medan. The object of this research is to improve students' mathematical communication skills by applying the Think-talk-write learning strategy. The instruments used in this study were observation and tests. This study consisted of 2 cycles and at the end of each cycle a mathematical communication ability test was given. Before being given, the test is first validated to the validator. The results of the research in cycle I obtained that students who understood aspects of writing reached 77.78% (medium category), students who were able to understand aspects of representation reached 59.26% (poor category), and classical completeness in cycle I reached 74.07% (category Enough). The results of the research in cycle II showed that students who understood aspects of writing reached 88.89% (good category), and students who were able to understand aspects of representation reached 85.19% (good category), and classical completeness in cycle II reached 88.89% ( good category).